2016
DOI: 10.18280/ijht.340405
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Parameters Governing 3D Laminar Mixed Convection Flow in a Rectangular Channel with Imposed Wall Flux Density

Abstract: A numerical study is carried out in order to understand the effect of the parameters governing three dimensional (3D) laminar mixed convection flows in a rectangular channel with imposed wall flux density. The mixed convection can be governed and influenced by many factors which appear in the conservation equations. In the literature, no unanimity is found on the formulation of these parameters which can affect the bouncy forces in the motion equation, and consequently the onset of the mixed convection regime,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…It is defined as the stress difference between the flow direction and the velocity gradient [20,21]. The concept of normal stress is directly reflected by pole climbing, jet swelling, floating siphon of non-Newtonian fluid.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…It is defined as the stress difference between the flow direction and the velocity gradient [20,21]. The concept of normal stress is directly reflected by pole climbing, jet swelling, floating siphon of non-Newtonian fluid.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The results showed that the use of SiO2-EG at a volume fraction of 6% and of 800 results in a higher average Nusselt number of about 50% compared to the case of using =100. Other interesting analysis of the effect of different techniques with and without nanofluids on enhancing heat transfer can be found in references [24][25][26]. Many studies investigated the effect of hydrodynamics on fish locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…Roy and Basak, [7]Studied numerically natural convection with uniform heating on the bottom and the vertical wall ,and also the non_uniform heating for different parameters Pr (0.2-100) and Ra (103-106). Benderradji et al [8]studied the effect of the variation of the two parameters (Grashof and Reynolds) in laminar mixed convection inside a cubic cavity.Aidaoui et al [9] made a numerical investigation of the parameter affecting 3D in a rectangular channel at constant flux density for laminar convection flow regime using CFD code. Oronzio et al [10] have been made an experimental mixed convection investigation in a vented cavity with forced flow entering throw the heated vertical wall side (experimental mixed convection.).…”
Section: Introductionmentioning
confidence: 99%